2013
DOI: 10.1007/s11095-013-1226-x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Delivery of pRNA Nanoparticles: Distribution and Clearance After Subconjunctival Injection

Abstract: Purpose RNA nanoparticles derived from the three-way junction (3WJ) of the pRNA of bacteriophage phi29 DNA packaging motor were previously found to be thermodynamically stable. As the nanoparticles could have potential in ocular drug delivery, the objectives in the present study were to investigate the distribution of pRNA nanoparticles after subconjunctival injection and examine the feasibility to deliver the nanoparticles to the cells of cornea and retina. Methods Alexa647-labeled pRNA nanoparticles (pRNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 41 publications
2
59
0
Order By: Relevance
“…A recent study revealed that pRNA nanoparticles can be delivered to the posterior of the eye and internalized into cornea and retina cells after subconjunctival injection [190] (Fig. 11).…”
Section: Methods and Current Achievements For Constructing Rna Namentioning
confidence: 99%
“…A recent study revealed that pRNA nanoparticles can be delivered to the posterior of the eye and internalized into cornea and retina cells after subconjunctival injection [190] (Fig. 11).…”
Section: Methods and Current Achievements For Constructing Rna Namentioning
confidence: 99%
“…Recently, Feng et al investigated the distribution and clearance of pRNA and dsRNA nanoparticles to the cornea and retina after subconjunctival injection. In vivo study was performed in mice and nanoparticles containing pRNA or dsRNA were labeled using Alexa647 for easy quantification and imaging [94]. Results indicated that pRNA and dsRNA were observed in sclera, corneal and conjunctiva cells, but only pRNA-X was detected in retinal cells [94].…”
Section: Novel Colloidal Delivery Systemsmentioning
confidence: 99%
“…In vivo study was performed in mice and nanoparticles containing pRNA or dsRNA were labeled using Alexa647 for easy quantification and imaging [94]. Results indicated that pRNA and dsRNA were observed in sclera, corneal and conjunctiva cells, but only pRNA-X was detected in retinal cells [94]. These results suggest that RNA therapy can be useful and delivered to the back-of-the-eye tissues for the treatment of posterior segment neovascular diseases.…”
Section: Novel Colloidal Delivery Systemsmentioning
confidence: 99%
“…The injection of non-viral RNA particles in the subconjunctival space showed appreciable transfection of cells in the retina, but the majority of the particles migrated towards the cornea (88). It is therefore not surprising, that this method has been mainly used in the delivery of gene therapy vectors for the cornea (101, 102), especially as only very small particles (20 nm diameter) seem to be able to successfully penetrate into the inner ocular tissue (103).…”
Section: Delivery Strategies For Non-viral Gene Therapy In the Retinamentioning
confidence: 99%